2011
DOI: 10.4236/jwarp.2011.36050
|View full text |Cite
|
Sign up to set email alerts
|

Application of Index Analysis to Evaluate the Water Quality of the Tuul River in Mongolia

Abstract: A study of water pollution determinands of the Tuul River was carried out in surrounding area of Ulaanbaatar, the capital of Mongolia at 14 monitoring sites, using an extensive dataset between 1998 and 2008. An index method, developed by Ministry of Nature and Environment of Mongolia, applied for assessment and total, seven hydro-chemicals used in the index calculation. The research indicates that the Tuul River is not polluted until the Ulaanbaatar city and the contamination level spike appears when the river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 11 publications
0
24
0
3
Order By: Relevance
“…Later, numerous researchers have carried out studies on water quality assessment using WQIs around the world in various water bodies (Pesce and Wunderlin 2000;Bordalo et al 2001;Abdul et al 2010;Akbal et al 2011;Altansukh and Davaa 2011;Hector et al 2012;Abdulwahid 2013;Mohamed et al 2014;Chrysoula et al 2014;Mehmet and Huseyin 2014;Will et al 2015;Gerald et al 2015;Hefni and Romanto 2015;Lobato et al 2015;Mehrnoosh et al 2015). Similarly, a number of studies have been carried out in India (Dwivedi and Pathak 2007;Joshi et al 2009;Samantray et al 2009;Chauhan and Singh 2010;Alam and Pathak 2010;Parmar and Parma 2010;Chaturvedi and Bassin 2010;Kalavathy et al 2011;Kankal et al 2012;Srinivas et al 2013;Prerna et al 2014;Salim and Ashok 2014;Jindal et al 2014;Mrunmayee et al 2015;Krishna et al 2014Krishna et al , 2015Kosha and Geeta 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Later, numerous researchers have carried out studies on water quality assessment using WQIs around the world in various water bodies (Pesce and Wunderlin 2000;Bordalo et al 2001;Abdul et al 2010;Akbal et al 2011;Altansukh and Davaa 2011;Hector et al 2012;Abdulwahid 2013;Mohamed et al 2014;Chrysoula et al 2014;Mehmet and Huseyin 2014;Will et al 2015;Gerald et al 2015;Hefni and Romanto 2015;Lobato et al 2015;Mehrnoosh et al 2015). Similarly, a number of studies have been carried out in India (Dwivedi and Pathak 2007;Joshi et al 2009;Samantray et al 2009;Chauhan and Singh 2010;Alam and Pathak 2010;Parmar and Parma 2010;Chaturvedi and Bassin 2010;Kalavathy et al 2011;Kankal et al 2012;Srinivas et al 2013;Prerna et al 2014;Salim and Ashok 2014;Jindal et al 2014;Mrunmayee et al 2015;Krishna et al 2014Krishna et al , 2015Kosha and Geeta 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The combined influences of land use alterations (the expansion of mining areas) and projected climate changes (the expected increased frequency of peak flow events; Altansukh and Davaa 2011;Törnqvist et al 2014) will likely result in increased discharge and erosion in the Lake Baikal drainage basin. Therefore, the transport of metals from the Zaamar site to the connected river systems will also likely increase.…”
Section: Impact Of Metal Speciation On Hydrological Transportmentioning
confidence: 99%
“…The Tuul River basin covers an area of approximately 50,000 km 2 , and the Sharyngol River basin is approximately half this size (MCA 2011). The activity of the numerous mining companies within the Zaamar Goldfield, along with illegal mining, is considered to have a serious impact on the water quality within the river basin (Altansukh and Davaa 2011;Chalov et al 2012;Thorslund et al 2012;Shinkareva et al 2015) and may have an impact on the downstream Selenga River and Lake Baikal. High levels of metals have been measured in the Tuul River (Lee et al 2006;AATA 2008), and previous mass balance quantifications have shown a net increase in metal loading, especially of metals in suspension, in the mining zone (Stubblefield et al 2005;Thorslund et al 2012).…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of its water sources meets the standards for drinking and industrial uses, with concentrations of total dissolved solids (TDS) ranging from 60 to 100 mg/L, remaining unaffected by sources of pollution in the city [10]. However, since the late 1990s, water quality in the downstream area of the Tuul River has deteriorated, due mainly to urban and industrial pollution [11][12][13][14][15]. Moreover, the unplanned expansion of Ger districts around the city has created a high potential for water contamination due to a lack of appropriate sanitation and sewage systems, which are based on pit latrines.…”
Section: Introductionmentioning
confidence: 99%